Animation Learning Media in Improving Narrative Writing Skills of Elementary School Students - Nurul Fauzia Ramadhani; Muhamad Adi Putra (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
Learning in elementary schools is carried out with the aim of teaching students writing skills. This writing skill is important to have because it is one of the four aspects of language skills. However, many studies report that students' narrative writing ability is still low, so efforts are needed to improve it. One effort that can be done to overcome these problems is to use animated learning media. This study aims to see how far the influence of the use of animated learning media on narrative writing skills of elementary school students. This research method uses a quantitative method with a quasi-experimental model with a non-equivalent control group design. This research was conducted at SD Negeri 064006 Medan Marelan. The sample in this study were fifth grade students as many as 50 respondents. The research instrument used was a description test through a post-test while the data analysis technique used descriptive quantitative. The results of this study indicate that students' narrative writing skills in classes that use animated learning media are better than classes that do not use animated learning media. The conclusion from this study is that animation learning media has an effect on developing students' narrative writing skills.